Coagulation disorder in newly diagnosed Overt Hypothyroid patients - Mou, Ummey Sabiha; Akhter, Qazi Shamima (Journal of Bangladesh Society of Physiologist, 2022)
Background: Various abnormalities of coagulation have been reported in patients with overt hypothyroidism. The coagulation abnormalities may result in mild bleeding tendency to profuse bleeding after any trauma or surgery in overt hypothyroid patients. Objective: To assess the coagulability status in overt hypothyroid patients by estimation of plasma factor VIII level and total count of platelets. Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from January 2016 to December 2016. Twenty overt hypothyroid patients with age ranging from 18 to 55 years were selected as study group and twenty healthy subjects were considered as control group. Patients were selected from Outpatients Department of Endocrinology and Nuclear Medicine & Allied Sciences of Dhaka Medical College Hospital, Dhaka. For assessment of coagulability state, plasma factor VIII level and total counts of platelet were estimated by automated analyzer. For statistical analysis unpaired Student ‘t’ test, Chi square test were used. Results: Total count of platelet and plasma factor VIII level were significantly lower (P<0.001) in overt hypothyroid patients. Conclusion: This study concluded that overt hypothyroid was associated with hypocoagulability and therefore these patients are at higher risk of bleeding tendency. J Bngladesh Soc Physiol 2021;16(1): 77-81